Visceral fat enhances blood pressure reactivity to physical but not mental challenges in male adolescents. Issue 5 (14th September 2015) - Van Woudenberg, M.; Abrahamowicz, M.; Leonard, G.; Perron, M.; Richer, L.; Veillette, S.; Gaudet, D.; Paus, T.; Pausova, Z.
Summary: Background: Excess visceral fat is a major risk factor for hypertension. Enhanced blood pressure (BP) reactivity and delayed BP recovery from physical and mental challenges predict future hypertension. Objectives: Determine whether visceral fat is associated with higher BP reactivity and delayed BP recovery from physical and mental challenges during adolescence. Methods: In a community‐based sample of 283 male and 308 female adolescents, we measured visceral fat with magnetic resonance imaging, total body fat with bioimpedance, and beat‐by‐beat BP with a Finometer at rest and during physical (10‐min standing) and mental (2‐min math stress) challenges. Results: Males vs. females showed greater BP reactivity and no differences in BP recovery from either type of challenges. Visceral fat was positively associated with BP reactivity to standing up only and in males only (+8.4 ± 3.6 mmHg per 1 log cm 3 of visceral fat, P = 0.008), and this association was independent of total body fat. No association was seen between visceral fat and BP recovery from either type of challenge in either sex. All these associations were independent of age, puberty stage, height and initial BP. Conclusions: Adolescent males vs. females demonstrate greater BP reactivity but similar BP recovery from physical and mental challenges. Excess visceral fat enhances BP reactivity to physical but not mental challenges in males only.